World Population Policies 2017: Highlights - United Nations Department of Economic; Social Affairs (United Nations, 2021)
This publication presents the highlights of the report World Population Policies 2017: Abortion Laws and Policies. It provides an overview of the laws and policies relating to induced abortion. It includes consideration of the various legal grounds and selected requirements for induced abortion, including gestational limits, the number of personnel required to authorise an abortion, mandatory third-party consent, and compulsory counselling and waiting periods.